2015
DOI: 10.3109/15569527.2015.1076433
|View full text |Cite
|
Sign up to set email alerts
|

Chronic liver injury in mice promotes impairment of skin barrier functionviatumor necrosis factor-alpha

Abstract: We propose a novel mechanism whereby plasma TNF-α, via TNFR2 alone or with TNFR1, plays an important role in skin barrier function during chronic liver disease in these mouse models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Previous studies have suggested mechanisms such as increased proinflammatory cytokines, eg, increased production of tumor necrosis factor -α (TNF-α) from peripheral blood monocytes and macrophages, and increased lymphocyte proliferation and activation, caused by alcohol 11. Alcohol-induced liver injury in mice resulted in an impairment of skin barrier function, possibly mediated via plasma TNF-α 12. Alcohol may also have an impact on the number and function of murine epidermal T cells 13.…”
Section: General Effects Of Alcoholmentioning
confidence: 99%
“…Previous studies have suggested mechanisms such as increased proinflammatory cytokines, eg, increased production of tumor necrosis factor -α (TNF-α) from peripheral blood monocytes and macrophages, and increased lymphocyte proliferation and activation, caused by alcohol 11. Alcohol-induced liver injury in mice resulted in an impairment of skin barrier function, possibly mediated via plasma TNF-α 12. Alcohol may also have an impact on the number and function of murine epidermal T cells 13.…”
Section: General Effects Of Alcoholmentioning
confidence: 99%
“…Experimental studies in mice have revealed that alcohol-induced liver injury can lead to damage of skin barrier unction, possibly mediated via plasma TNF-α [61], whereas it has also been shown that alcohol and can influence the number and function of epidermal T cells [62] and can reduce dendritic function in female mice [63]. Moreover, alcohol can influence migration of murine dermal dendritic cells to draining lymph nodes after sensitization [64].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the skin of ethanol-administrated hairless mice is characterized by attenuated skin hydration with significantly increased transepidermal water loss, up-regulated expression of TNF receptor 2 (TNFR2), decreased production of ceramide and type I collagen and increased plasma TNFα concentrations. In addition, anti-TNFα antibody treatment ameliorated the impaired skin barrier function in these mice [39]. Chronic ethanol feeding negatively affects both the number and the function of murine epidermal and dermal T cell subsets [40].…”
Section: Alcohol and The Immune Systemmentioning
confidence: 94%